A Collaborative Initiative for Reducing Operating Room Waste of Unused Refrigerated Medication. (December 2020) - Tsang, Dawn K.; Deng, Jin; Enten, Garrett; Coleman, Debra; Dansby, Mary; Pease, Sonya; Camporesi, Enrico M.
Background: Inappropriate management of anesthetic medications requiring refrigeration creates waste and increases costs of intraoperative care. At Tampa General Hospital, pharmacy personnel refill medications in cardiovascular operating rooms (CVOR) nightly and noticed large amounts of unattended medications at room temperature for unknown periods of time. Per protocol, these medications were disposed. Objective: To effectively decrease pharmaceutical waste in the CVOR. Methods: A pharmacy-led anesthesia committee identified the most used intraoperative medications requiring refrigeration and implemented changes to decrease waste. As a result, norepinephrine intravenous piggyback (IVPB), norepinephrine vials, nitroglycerin vials, and epinephrine IVPB were physically relocated into preexisting mini-refrigerators inside each CVOR. Vasopressin vials and phenylephrine syringes/vials were relocated into automated anesthesia cabinets. Amounts and cost of wasted medication were analyzed before and after protocol implementation. Results: Average weekly cost of wasted medication was significantly reduced (preintervention: US$1188.59 vs postintervention: US$322.96; P < .001), despite a consistent caseload. Conclusion: Recorded weekly savings of US$865.63 (∼annual savings of >US$45 000) reflect only the explicit cost of waste. True savings are higher when including opportunity costs such as salary of pharmacy personnel and supplies needed to replace wasted medications. We demonstrate the benefits of a collaborative approach to improving inefficiencies in health care.